Cooling forests, calmer hearts: Urban forest structure, microclimate and heat relief in adolescents - Sophie Feiertag; Daniel A. Scheller; Jan Schmid-Ellinger; Anna-Katharina Eisen; Filip Mess; Annette Menzel (Urban Forestry & Urban Greening, 2026)

Comparison of chilling requirements of boreal and temperate tree species in Germany and North America - Claudia Nanninga; Rebecca A. Montgomery; Annette Menzel; Julia Laube (International Journal of Biometeorology, 2026)
Chilling is an important cue in the spring phenology of boreal and temperate tree species. It is well established that increased chilling reduces the days to bud break (DTB), but the effectiveness of different cold temperatures for chilling accumulation remains unknown for most species. Depending on this effectiveness, future warmer winters could either reduce or increase chilling accumulation for different tree species, resulting in delayed or advanced bud break. This could alter primary productivity and ecological interactions. We investigated chilling effects on DTB experimentally, using twigs of boreal and temperate tree species in Minnesota, USA. (8 species), and Bavaria, Germany (6 species). We collected twigs and applied artificial chilling in cooling chambers at three different temperatures (-7/-6.5 °C; 1.5/2°C; 4.5/4°C - USA/Germany) and with two different lengths (4/8 weeks), before placing them into forcing chambers at 21 °C/16°C, 16 h photoperiod. We additionally took twigs from the same locations on three different dates and immediately placed them into the forcing chambers. In both experiments, we observed DTB. Both experiments showed that longer chilling exposure reduced DTB and that temperatures below freezing contributed to chilling accumulation. Changing the chilling temperatures had a significant effect on DTB for 8 out of the 14 species. For most species, higher chilling temperatures more effectively reduced DTB than colder temperatures. With few exceptions, species growing in Germany required less chilling, and boreal species broke bud before temperate species. Our study confirms the need to understand species-specific chilling requirements since generalizations seem inappropriate when predicting future leaf out.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Decreasing frequency and extent of frost damage in European oaks over 1961-2021 - Jianhong Lin; Nicolas Delpierre; Fabien Caroulle; Sebastien Cecchini; Vincent Badeau; Thomas Caignard; Daniel Berveiller; Sylvain Delzon; Heikki Hänninen; Antoine Kremer; Annette Menzel; Alexandre Morfin; et al. (Agricultural and Forest Meteorology, 2026)

Determinants of tree regeneration in degraded temperate floodplain forests under recent passive conservation - Clemens Detsch; Korbinian Tartler; Anna-Katharina Eisen; Johannes Kollmann; Tobias Fuchs; Sophie Feiertag; Andreas Rothe; Annette Menzel; Peter Annighöfer (Forest Ecology and Management, 2025)

A multi-scale analysis of airborne Alternaria spore dispersal: influence of meteorology, land cover and air pollution - Maria P. Plaza; Jose Oteros; Vivien Leier-Wirtz; Franziska Kolek; Annette Menzel; Jeroen T.M. Buters; Claudia Traidl-Hoffmann; Athanasios Damialis (Agricultural and Forest Meteorology, 2025)

When considering uncertainty, agroforestry can reduce trade-offs between economic and ecological benefits - Thomas Knoke; Carola Paul; Elizabeth Gosling; Esther Reith; Peter Annighöfer; Senthold Asseng; Logan Bingham; Lucie Chmelikova; Fabian Frick; Benjamin D. Hafner; Sara Diana Leonhardt; Luisa Menapace; et al. (Agroforestry Systems, 2025)
Persistent uncertainty about the economic implications of agroforestry presents a significant barrier to adoption. Despite this, most research to date ignores the impact of uncertainty on land allocation decisions, with studies commonly relying on simplistic scenarios involving a dichotomous choice between switching entirely to agroforestry or retaining the status quo system. For a more realistic decision problem, we explored partial adoption choices by analysing how the performance of landscape portfolios under combined ecological and economic uncertainty changes when managers can incorporate two agroforestry alternatives (silvopasture and alley cropping) alongside existing land-use options. Drawing on published data from smallholders in Panama, we used robust optimisation of multiple objectives to allocate fractions of land area across six agroforestry and non-agroforestry land uses under a range of possible futures. We visualised trade-offs between uncertain ecological and economic benefits using robust Pareto frontiers. We found that neglecting uncertainty reduces the attractiveness of agroforestry. Instead, agroforestry became increasingly competitive as uncertainty grew, and incorporating it into landscape portfolios could mitigate trade-offs between ecological and economic objectives when the future is uncertain. At the same time, we argue that agroforestry-uncertainty relationships are multi-layered. Early-life information is largely missing, and discontinuous cash flows, deficiencies in modelling, and a lack of financial incentives contribute to the uncertainty of agroforestry land uses and their barriers to broader adoption under global change.

The linkage between functional traits and drone-derived phenology of 74 Northern Hemisphere tree species - Simon Kloos; Marvin Lüpke; Nicole Estrella; Wael Ghada; Jens Kattge; Solveig Franziska Bucher; Allan Buras; Annette Menzel (Science of The Total Environment, 2024)

No Future Growth Enhancement Expected at the Northern Edge for European Beech due to Continued Water Limitation - Stefan Klesse; Richard L. Peters; Raquel Alfaro‐Sánchez; Vincent Badeau; Claudia Baittinger; Giovanna Battipaglia; Didier Bert; Franco Biondi; Michal Bosela; Marius Budeanu; Vojtěch Čada; J. Julio Camarero; et al. (Global Change Biology, 2024)
With ongoing global warming, increasing water deficits promote physiological stress on forest ecosystems with negative impacts on tree growth, vitality, and survival. How individual tree species will react to increased drought stress is therefore a key research question to address for carbon accounting and the development of climate change mitigation strategies. Recent tree‐ring studies have shown that trees at higher latitudes will benefit from warmer temperatures, yet this is likely highly species‐dependent and less well‐known for more temperate tree species. Using a unique pan‐European tree‐ring network of 26,430 European beech ( Fagus sylvatica L. ) trees from 2118 sites, we applied a linear mixed‐effects modeling framework to (i) explain variation in climate‐dependent growth and (ii) project growth for the near future (2021–2050) across the entire distribution of beech. We modeled the spatial pattern of radial growth responses to annually varying climate as a function of mean climate conditions (mean annual temperature, mean annual climatic water balance, and continentality). Over the calibration period (1952–2011), the model yielded high regional explanatory power ( R 2 = 0.38–0.72). Considering a moderate climate change scenario (CMIP6 SSP2‐4.5), beech growth is projected to decrease in the future across most of its distribution range. In particular, projected growth decreases by 12%–18% (interquartile range) in northwestern Central Europe and by 11%–21% in the Mediterranean region. In contrast, climate‐driven growth increases are limited to around 13% of the current occurrence, where the historical mean annual temperature was below ~6°C. More specifically, the model predicts a 3%–24% growth increase in the high‐elevation clusters of the Alps and Carpathian Arc. Notably, we find little potential for future growth increases (−10 to +2%) at the poleward leading edge in southern Scandinavia. Because in this region beech growth is found to be primarily water‐limited, a northward shift in its distributional range will be constrained by water availability.

Identifying drivers of non-stationary climate-growth relationships of European beech - Christopher Leifsson; Allan Buras; Stefan Klesse; Claudia Baittinger; Banzragch Bat-Enerel; Giovanna Battipaglia; Franco Biondi; Branko Stajić; Marius Budeanu; Vojtěch Čada; Liam Cavin; Hugues Claessens; et al. (Science of The Total Environment, 2024)

Revealing legacy effects of extreme droughts on tree growth of oaks across the Northern Hemisphere - Arun K. Bose; Jiri Doležal; Daniel Scherrer; Jan Altman; Daniel Ziche; Elisabet Martínez-Sancho; Christof Bigler; Andreas Bolte; Michele Colangelo; Isabel Dorado-Liñán; Igor Drobyshev; Sophia Etzold; et al. (Science of The Total Environment, 2024)

Decoding autumn phenology: Unraveling the link between observation methods and detected environmental cues - Simon Kloos; Anne Klosterhalfen; Alexander Knohl; Annette Menzel (Global Change Biology, 2024)
Leaf coloring and fall mark the end of the growing season (EOS), playing essential roles in nutrient cycling, resource allocation, ecological interactions, and as climate change indicators. However, understanding future changes in autumn phenology is challenging due to the multitude of likely environmental cues and substantial variations in timing caused by different derivation methods. Yet, it remains unclear whether these two factors are independent or if methodological uncertainties influence the environmental cues determined. We derived start of growing season (SOS) and EOS at a mixed beech forest in Central Germany for the period 2000–2020 based on four different derivation methods using a unique long‐term data set of in‐situ data, canopy imagery, eddy covariance measurements, and satellite remote sensing data and determined their influence on a predictor analysis of leaf senescence. Both SOS and EOS exhibited substantial ranges in mean onset dates (39.5 and 28.6 days, respectively) across the different methods, although inter‐annual variations and advancing SOS trends were similar across methods. Depending on the data, EOS trends were advanced or delayed, but inter‐annual patterns correlated well (mean r = .46). Overall, warm, dry, and less photosynthetically productive growing seasons were more likely to be associated with a delayed EOS, while colder, wetter, and more photosynthetically productive vegetation periods resulted in an earlier EOS. In addition, contrary to recent results, no clear influence of pre‐solstice vegetation activity on the timing of senescence was detected. However, most notable were the large differences in sign and strength of potential drivers both in the univariate and multivariate analyses when comparing derivation methodologies. The results suggest that an ensemble analysis of all available phenological data sources and derivation methods is needed for general statements on autumn phenology and its influencing variables and correct implementation of the senescence process in ecosystem models.

Weather, weekday, and vacation effects on webcam recorded daily visitor numbers in the alpine winter season - Simon Kloos; Carina Bigalke; Matthias Neumair; Annette Menzel (International Journal of Biometeorology, 2024)
Winter tourism is an important economic factor in the European Alps, which could be exposed to severely changing meteorological conditions due to climate change in the future. The extent to which meteorology influences winter tourism figures has so far been analyzed mainly based on monthly or seasonal data and in relation to skier numbers. Therefore, we record for the first time daily visitor numbers at five Bavarian winter tourism destinations based on 1518 webcam images using object detection and link them to meteorological and time-related variables. Our results show that parameters such as temperature, cloud cover or sunshine duration, precipitation, snow depth, wind speed, and relative humidity play a role especially at locations that include other forms of winter tourism in addition to skiing. In the ski resorts studied, on the other hand, skiing is mostly independent of current weather conditions, which can be attributed mainly to artificial snowmaking. Moreover, at the webcam sites studied, weekends and vacation periods had an equal or even stronger influence on daily visitor numbers than the current weather conditions. The extent to which weather impacts the (future) visitor numbers of a winter tourism destination must therefore be investigated individually and with the inclusion of non-meteorological variables influencing human behavior.

Establishing the twig method for investigations on pollen characteristics of allergenic tree species - Stephan Jung; Feng Zhao; Annette Menzel (International Journal of Biometeorology, 2021)
The twig method in climate chambers has been shown to successfully work as a proxy for outdoor manipulations in various experimental setups. This study was conducted to further establish this method for the investigation of allergenic pollen from tree species (hazel, alder, and birch). Direct comparison under outdoor conditions revealed that the cut twigs compared to donor trees were similar in the timing of flowering and the amount of pollen produced. Cut twigs were able to flower in climate chambers and produced a sufficient amount of pollen for subsequent laboratory analysis. The addition of different plant or tissue fertilizers in the irrigation of the twigs did not have any influence; rather, the regular exchange of water and the usage of fungicide were sufficient for reaching the stage of flowering. In the experimental setup, the twigs were cut in different intervals before the actual flowering and were put under warming conditions in the climate chamber. An impact of warming on the timing of flowering/pollen characteristics could be seen for the investigated species. Therefore, the twig method is well applicable for experimental settings in pollen research simulating, e.g., accelerated warming under climate change.

Effects of future climate change on birch abundance and their pollen load - Jesús Rojo; Jose Oteros; Antonio Picornell; José M. Maya‐Manzano; Athanasios Damialis; Katrin Zink; Matthias Werchan; Barbora Werchan; Matt Smith; Annette Menzel; Sabine Timpf; Claudia Traidl‐Hoffmann; et al. (Global Change Biology, 2021)
Climate change impacts on the structure and function of ecosystems will worsen public health issues like allergic diseases. Birch trees ( Betula spp.) are important sources of aeroallergens in Central and Northern Europe. Birches are vulnerable to climate change as these trees are sensitive to increased temperatures and summer droughts. This study aims to examine the effect of climate change on airborne birch pollen concentrations in Central Europe using Bavaria in Southern Germany as a case study. Pollen data from 28 monitoring stations in Bavaria were used in this study, with time series of up 30 years long. An integrative approach was used to model airborne birch pollen concentrations taking into account drivers influencing birch tree abundance and birch pollen production and projections made according to different climate change and socioeconomic scenarios. Birch tree abundance is projected to decrease in parts of Bavaria at different rates, depending on the climate scenario, particularly in current centres of the species distribution. Climate change is expected to result in initial increases in pollen load but, due to the reduction in birch trees, the amount of airborne birch pollen will decrease at lower altitudes. Conversely, higher altitude areas will experience expansions in birch tree distribution and subsequent increases in airborne birch pollen in the future. Even considering restrictions for migration rates, increases in pollen load are likely in Southwestern areas, where positive trends have already been detected during the last three decades. Integrating models for the distribution and abundance of pollen sources and the drivers that control birch pollen production allowed us to model airborne birch pollen concentrations in the future. The magnitude of changes depends on location and climate change scenario.

Maps, trends, and temperature sensitivities—phenological information from and for decreasing numbers of volunteer observers - Ye Yuan; Stefan Härer; Tobias Ottenheym; Gourav Misra; Alissa Lüpke; Nicole Estrella; Annette Menzel (International Journal of Biometeorology, 2021)
Phenology serves as a major indicator of ongoing climate change. Long-term phenological observations are critically important for tracking and communicating these changes. The phenological observation network across Germany is operated by the National Meteorological Service with a major contribution from volunteering activities. However, the number of observers has strongly decreased for the last decades, possibly resulting in increasing uncertainties when extracting reliable phenological information from map interpolation. We studied uncertainties in interpolated maps from decreasing phenological records, by comparing long-term trends based on grid-based interpolated and station-wise observed time series, as well as their correlations with temperature. Interpolated maps in spring were characterized by the largest spatial variabilities across Bavaria, Germany, with respective lowest interpolated uncertainties. Long-term phenological trends for both interpolations and observations exhibited mean advances of −0.2 to −0.3 days year −1 for spring and summer, while late autumn and winter showed a delay of around 0.1 days year −1 . Throughout the year, temperature sensitivities were consistently stronger for interpolated time series than observations. Such a better representation of regional phenology by interpolation was equally supported by satellite-derived phenological indices. Nevertheless, simulation of observer numbers indicated that a decline to less than 40% leads to a strong decrease in interpolation accuracy. To better understand the risk of declining phenological observations and to motivate volunteer observers, a Shiny app is proposed to visualize spatial and temporal phenological patterns across Bavaria and their links to climate change–induced temperature changes.

Climate warming increases spring phenological differences among temperate trees - Xiaojun Geng; Yongshuo H. Fu; Fanghua Hao; Xuancheng Zhou; Xuan Zhang; Guodong Yin; Yann Vitasse; Shilong Piao; Kechang Niu; Hans J. De Boeck; Annette Menzel; Josep Peñuelas (Global Change Biology, 2020)
Climate warming has substantially advanced spring leaf flushing, but winter chilling and photoperiod co‐determine the leaf flushing process in ways that vary among species. As a result, the interspecific differences in spring phenology (IDSP) are expected to change with climate warming, which may, in turn, induce negative or positive ecological consequences. However, the temporal change of IDSP at large spatiotemporal scales remains unclear. In this study, we analyzed long‐term in‐situ observations (1951–2016) of six, coexisting temperate tree species from 305 sites across Central Europe and found that phenological ranking did not change when comparing the rapidly warming period 1984–2016 to the marginally warming period 1951–1983. However, the advance of leaf flushing was significantly larger in early‐flushing species EFS (6.7 ± 0.3 days) than in late‐flushing species LFS (5.9 ± 0.2 days) between the two periods, indicating extended IDSP. This IDSP extension could not be explained by differences in temperature sensitivity between EFS and LFS; however, climatic warming‐induced heat accumulation effects on leaf flushing, which were linked to a greater heat requirement and higher photoperiod sensitivity in LFS, drove the shifts in IDSP. Continued climate warming is expected to further extend IDSP across temperate trees, with associated implications for ecosystem function.

Does Coltsfoot ( Tussilago farfara L.) have an autumn temperature control to limit precocious flowering in spring? - Tim H. Sparks; Allan Buras; Nicole Estrella; Annette Menzel (International Journal of Climatology, 2020)
The flowering phenology of Coltsfoot ( Tussilago farfara L.) shows a very strong negative response to warmer temperatures in spring (warmer springs = earlier flowering) as reported in numerous studies for other species in Europe and North America. However, despite this, flowering dates in some locations have failed to show a strong advance and, in a small number of cases, have even shown significant delays. Here we use a very extensive data set on first flowering dates (FFD) of Coltsfoot in Germany, firstly on a national scale in the period 1894–2015 and secondly at a regional level in the more thoroughly recorded period from 1951–2015. FFDs were coupled with gridded temperature data using regression techniques to attempt to understand the reasons for the unexpected changes in phenology. National mean FFD did not change significantly over 122 years, although January–March mean temperatures had warmed by 1.2°C. The flowering‐temperature model was significantly improved when the previous September mean temperature was included, which decreased the overall temperature response from 4.5 to 3.7 days/°C. For the more thoroughly recorded period of 1951–2015, January–March mean temperature warmed significantly by 1.7–2.4°C in all 11 German federal state combinations and mean FFD dates advanced by 3–14 days, significant for seven of the States. For 10 of the 11 States, multiple linear regressions explained 79–89% of the observed variation in FFD and evidenced a positive relationship (significant in half of these) with higher temperature in the September preceding flowering (warmer September = later flowering). However, the scale of the September influence is insufficient to explain why Coltsfoot flowering may have stalled or been delayed. The use of controlled experiments to supplement observational data may be necessary to fully understand the drivers of Coltsfoot flowering in spring.

Nutrients and water availability constrain the seasonality of vegetation activity in a Mediterranean ecosystem - Yunpeng Luo; Tarek El‐Madany; Xuanlong Ma; Richard Nair; Martin Jung; Ulrich Weber; Gianluca Filippa; Solveig F. Bucher; Gerardo Moreno; Edoardo Cremonese; Arnaud Carrara; Rosario Gonzalez‐Cascon; et al. (Global Change Biology, 2020)
Anthropogenic nitrogen (N) deposition and resulting differences in ecosystem N and phosphorus (P) ratios are expected to impact photosynthetic capacity, that is, maximum gross primary productivity (GPP max ). However, the interplay between N and P availability with other critical resources on seasonal dynamics of ecosystem productivity remains largely unknown. In a Mediterranean tree–grass ecosystem, we established three landscape‐level (24 ha) nutrient addition treatments: N addition (NT), N and P addition (NPT), and a control site (CT). We analyzed the response of ecosystem to altered nutrient stoichiometry using eddy covariance fluxes measurements, satellite observations, and digital repeat photography. A set of metrics, including phenological transition dates (PTDs; timing of green‐up and dry‐down), slopes during green‐up and dry‐down period, and seasonal amplitude, were extracted from time series of GPP max and used to represent the seasonality of vegetation activity. The seasonal amplitude of GPP max was higher for NT and NPT than CT, which was attributed to changes in structure and physiology induced by fertilization. PTDs were mainly driven by rainfall and exhibited no significant differences among treatments during the green‐up period. Yet, both fertilized sites senesced earlier during the dry‐down period (17–19 days), which was more pronounced in the NT due to larger evapotranspiration and water usage. Fertilization also resulted in a faster increase in GPP max during the green‐up period and a sharper decline in GPP max during the dry‐down period, with less prominent decline response in NPT. Overall, we demonstrated seasonality of vegetation activity was altered after fertilization and the importance of nutrient–water interaction in such water‐limited ecosystems. With the projected warming‐drying trend, the positive effects of N fertilization induced by N deposition on GPP max may be counteracted by an earlier and faster dry‐down in particular in areas where the N:P ratio increases, with potential impact on the carbon cycle of water‐limited ecosystems.

Growth and resilience responses of Scots pine to extreme droughts across Europe depend on predrought growth conditions - Arun K. Bose; Arthur Gessler; Andreas Bolte; Alessandra Bottero; Allan Buras; Maxime Cailleret; J. Julio Camarero; Matthias Haeni; Ana‐Maria Hereş; Andrea Hevia; Mathieu Lévesque; Juan C. Linares; et al. (Global Change Biology, 2020)
Global climate change is expected to further raise the frequency and severity of extreme events, such as droughts. The effects of extreme droughts on trees are difficult to disentangle given the inherent complexity of drought events (frequency, severity, duration, and timing during the growing season). Besides, drought effects might be modulated by trees’ phenotypic variability, which is, in turn, affected by long‐term local selective pressures and management legacies. Here we investigated the magnitude and the temporal changes of tree‐level resilience (i.e., resistance, recovery, and resilience) to extreme droughts. Moreover, we assessed the tree‐, site‐, and drought‐related factors and their interactions driving the tree‐level resilience to extreme droughts. We used a tree‐ring network of the widely distributed Scots pine ( Pinus sylvestris ) along a 2,800 km latitudinal gradient from southern Spain to northern Germany. We found that the resilience to extreme drought decreased in mid‐elevation and low productivity sites from 1980–1999 to 2000–2011 likely due to more frequent and severe droughts in the later period. Our study showed that the impact of drought on tree‐level resilience was not dependent on its latitudinal location, but rather on the type of sites trees were growing at and on their growth performances (i.e., magnitude and variability of growth) during the predrought period. We found significant interactive effects between drought duration and tree growth prior to drought, suggesting that Scots pine trees with higher magnitude and variability of growth in the long term are more vulnerable to long and severe droughts. Moreover, our results indicate that Scots pine trees that experienced more frequent droughts over the long‐term were less resistant to extreme droughts. We, therefore, conclude that the physiological resilience to extreme droughts might be constrained by their growth prior to drought, and that more frequent and longer drought periods may overstrain their potential for acclimation.

Climate change fingerprints in recent European plant phenology - Annette Menzel; Ye Yuan; Michael Matiu; Tim Sparks; Helfried Scheifinger; Regula Gehrig; Nicole Estrella (Global Change Biology, 2020)
A paper published in Global Change Biology in 2006 revealed that phenological responses in 1971–2000 matched the warming pattern in Europe, but a lack of chilling and adaptation in farming may have reversed these findings. Therefore, for 1951–2018 in a corresponding data set, we determined changes as linear trends and analysed their variation by plant traits/groups, across season and time as well as their attribution to warming following IPCC methodology. Although spring and summer phases in wild plants advanced less (maximum advances in 1978–2007), more (~90%) and more significant (~60%) negative trends were present, being stronger in early spring, at higher elevations, but smaller for nonwoody insect‐pollinated species. These trends were strongly attributable to winter and spring warming. Findings for crop spring phases were similar, but were less pronounced. There were clearer and attributable signs for a delayed senescence in response to winter and spring warming. These changes resulted in a longer growing season, but a constant generative period in wild plants and a shortened one in agricultural crops. Phenology determined by farmers’ decisions differed noticeably from the purely climatic driven phases with smaller percentages of advancing (~75%) trends, but farmers’ spring activities were the only group with reinforced advancement, suggesting adaptation. Trends in farmers’ spring and summer activities were very likely/likely associated with the warming pattern. In contrast, the advance in autumn farming phases was significantly associated with below average summer warming. Thus, under ongoing climate change with decreased chilling the advancing phenology in spring and summer is still attributable to warming; even the farmers’ activities in these seasons mirror, to a lesser extent, the warming. Our findings point to adaptation to climate change in agriculture and reveal diverse implications for terrestrial ecosystems; the strong attribution supports the necessary mediation of warming impacts to the general public.

Pollen forecasts in complex topography: two case studies from the Alps using the numerical pollen forecast model COSMO-ART - Andreas Pauling; Bernard Clot; Annette Menzel; Stephan Jung (Aerobiologia, 2020)

Regional trend changes in recent surface warming - Christian S. Zang; Susanne Jochner-Oette; José Cortés; Anja Rammig; Annette Menzel (Climate Dynamics, 2019)

Geographical adaptation prevails over species‐specific determinism in trees’ vulnerability to climate change at Mediterranean rear‐edge forests - Isabel Dorado‐Liñán; Gianluca Piovesan; Elisabet Martínez‐Sancho; Guillermo Gea‐Izquierdo; Christian Zang; Isabel Cañellas; Daniele Castagneri; Alfredo Di Filippo; Emilia Gutiérrez; Joerg Ewald; Laura Fernández‐de‐Uña; Daniel Hornstein; et al. (Global Change Biology, 2019)
Climate change may reduce forest growth and increase forest mortality, which is connected to high carbon costs through reductions in gross primary production and net ecosystem exchange. Yet, the spatiotemporal patterns of vulnerability to both short‐term extreme events and gradual environmental changes are quite uncertain across the species’ limits of tolerance to dryness. Such information is fundamental for defining ecologically relevant upper limits of species tolerance to drought and, hence, to predict the risk of increased forest mortality and shifts in species composition. We investigate here to what extent the impact of short‐ and long‐term environmental changes determines vulnerability to climate change of three evergreen conifers (Scots pine, silver fir, Norway spruce) and two deciduous hardwoods (European beech, sessile oak) tree species at their southernmost limits of distribution in the Mediterranean Basin. Finally, we simulated future forest growth under RCP 2.6 and 8.5 emission scenarios using a multispecies generalized linear mixed model. Our analysis provides four key insights into the patterns of species’ vulnerability to climate change. First, site climatic marginality was significantly linked to the growth trends: increasing growth was related to less climatically limited sites. Second, estimated species‐specific vulnerability did not match their a priori rank in drought tolerance: Scots pine and beech seem to be the most vulnerable species among those studied despite their contrasting physiologies. Third, adaptation to site conditions prevails over species‐specific determinism in forest response to climate change. And fourth, regional differences in forests vulnerability to climate change across the Mediterranean Basin are linked to the influence of summer atmospheric circulation patterns, which are not correctly represented in global climate models. Thus, projections of forest performance should reconsider the traditional classification of tree species in functional types and critically evaluate the fine‐scale limitations of the climate data generated by global climate models.

Decrease or increase? Temporal changes in pollen concentrations assessed by Bayesian statistics - Susanne Jochner-Oette; Annette Menzel; Regula Gehrig; Bernard Clot (Aerobiologia, 2019)

Climatically controlled reproduction drives interannual growth variability in a temperate tree species - Andrew J. Hacket‐Pain; Davide Ascoli; Giorgio Vacchiano; Franco Biondi; Liam Cavin; Marco Conedera; Igor Drobyshev; Isabel Dorado Liñán; Andrew D. Friend; Michael Grabner; Claudia Hartl; Juergen Kreyling; et al. (Ecology Letters, 2018)
Climatically controlled allocation to reproduction is a key mechanism by which climate influences tree growth and may explain lagged correlations between climate and growth. We used continent‐wide datasets of tree‐ring chronologies and annual reproductive effort in Fagus sylvatica from 1901 to 2015 to characterise relationships between climate, reproduction and growth. Results highlight that variable allocation to reproduction is a key factor for growth in this species, and that high reproductive effort (‘mast years’) is associated with stem growth reduction. Additionally, high reproductive effort is associated with previous summer temperature, creating lagged climate effects on growth. Consequently, understanding growth variability in forest ecosystems requires the incorporation of reproduction, which can be highly variable. Our results suggest that future response of growth dynamics to climate change in this species will be strongly influenced by the response of reproduction.

Increased water‐use efficiency translates into contrasting growth patterns of Scots pine and sessile oak at their southern distribution limits - Elisabet Martínez‐Sancho; Isabel Dorado‐Liñán; Emilia Gutiérrez Merino; Michael Matiu; Gerhard Helle; Ingo Heinrich; Annette Menzel (Global Change Biology, 2018)
In forests, the increase in atmospheric CO 2 concentrations ( C a ) has been related to enhanced tree growth and intrinsic water‐use efficiency ( iWUE ). However, in drought‐prone areas such as the Mediterranean Basin, it is not yet clear to what extent this “fertilizing” effect may compensate for drought‐induced growth reduction. We investigated tree growth and physiological responses at five Scots pine ( Pinus sylvestris L.) and five sessile oak ( Quercus petraea (Matt.) Liebl.) sites located at their southernmost distribution limits in Europe for the period 1960–2012 using annually resolved tree‐ring width and δ 13 C data to track ecophysiological processes. Results indicated that all 10 natural stands significantly increased their leaf intercellular CO 2 concentration ( C i ), and consequently iWUE . Different trends in the theoretical gas‐exchange scenarios as a response to increasing C a were found: generally, C i tended to increase proportionally to C a , except for trees at the driest sites in which C i remained constant. C i from the oak sites displaying higher water availability tended to increase at a comparable rate to C a . Multiple linear models fitted at site level to predict basal area increment ( BAI ) using iWUE and climatic variables better explained tree growth in pines (31.9%–71.4%) than in oak stands (15.8%–46.8%). iWUE was negatively linked to pine growth, whereas its effect on growth of oak differed across sites. Tree growth in the western and central oak stands was negatively related to iWUE , whereas BAI from the easternmost stand was positively associated with iWUE . Thus, some Q. petraea stands might have partially benefited from the “fertilizing” effect of rising C a , whereas P. sylvestris stands due to their strict closure of stomata did not profit from increased iWUE and consequently showed in general growth reductions across sites. Additionally, the inter‐annual variability of BAI and iWUE displayed a geographical polarity in the Mediterranean.

Soil water storage appears to compensate for climatic aridity at the xeric margin of European tree species distribution - Karl H. Mellert; Jonathan Lenoir; Susanne Winter; Christian Kölling; Andraž Čarni; Isabel Dorado-Liñán; Jean-Claude Gégout; Axel Göttlein; Daniel Hornstein; Matthias Jantsch; Nina Juvan; Eckart Kolb; et al. (European Journal of Forest Research, 2018)

Changes in spring arrival dates and temperature sensitivity of migratory birds over two centuries - Eva Kolářová; Michael Matiu; Annette Menzel; Jiří Nekovář; Petr Lumpe; Peter Adamík (International Journal of Biometeorology, 2017)

Elevational response in leaf and xylem phenology reveals different prolongation of growing period of common beech and Norway spruce under warming conditions in the Bavarian Alps - Christina Kraus; Christian Zang; Annette Menzel (European Journal of Forest Research, 2016)

Long-term linear trends mask phenological shifts - Yongshuo H Fu; Shilong Piao; Philippe Ciais; Mengtian Huang; Annette Menzel; Marc Peaucelle; Shushi Peng; Yang Song; Yann Vitasse; Zhenzhong Zeng; Hongfang Zhao; Guiyun Zhou; et al. (International Journal of Biometeorology, 2016)

Can we detect a nonlinear response to temperature in European plant phenology? - Susanne Jochner; Tim H. Sparks; Julia Laube; Annette Menzel (International Journal of Biometeorology, 2016)

Climatic marginality: a new metric for the susceptibility of tree species to warming exemplified by Fagus sylvatica (L.) and Ellenberg’s quotient - Karl H. Mellert; Jörg Ewald; Daniel Hornstein; Isabel Dorado-Liñán; Matthias Jantsch; Steffen Taeger; Christian Zang; Annette Menzel; Christian Kölling (European Journal of Forest Research, 2016)

Asymmetric trends in seasonal temperature variability in instrumental records from ten stations in Switzerland, Germany and the UK from 1864 to 2012 - Michael Matiu; Donna P. Ankerst; Annette Menzel (International Journal of Climatology, 2016)

Climate sensitivity and variation in first flowering of 26 Narcissus cultivars - Anna Bock; Tim H. Sparks; Nicole Estrella; Nigel Jee; Andrew Casebow; Michael Leuchner; Annette Menzel (International Journal of Biometeorology, 2015)

Twenty years of successful papers in Global Change Biology - Annette Menzel; Michael Matiu; Tim H. Sparks (Global Change Biology, 2014)

Patterns of drought tolerance in major European temperate forest trees: climatic drivers and levels of variability - Christian Zang; Claudia Hartl‐Meier; Christoph Dittmar; Andreas Rothe; Annette Menzel (Global Change Biology, 2014)
The future performance of native tree species under climate change conditions is frequently discussed, since increasingly severe and more frequent drought events are expected to become a major risk for forest ecosystems. To improve our understanding of the drought tolerance of the three common European temperate forest tree species Norway spruce, silver fir and common beech, we tested the influence of climate and tree‐specific traits on the inter and intrasite variability in drought responses of these species. Basal area increment data from a large tree‐ring network in Southern Germany and Alpine Austria along a climatic cline from warm‐dry to cool‐wet conditions were used to calculate indices of tolerance to drought events and their variability at the level of individual trees and populations. General patterns of tolerance indicated a high vulnerability of Norway spruce in comparison to fir and beech and a strong influence of bioclimatic conditions on drought response for all species. On the level of individual trees, low‐growth rates prior to drought events, high competitive status and low age favored resilience in growth response to drought. Consequently, drought events led to heterogeneous and variable response patterns in forests stands. These findings may support the idea of deliberately using spontaneous selection and adaption effects as a passive strategy of forest management under climate change conditions, especially a strong directional selection for more tolerant individuals when frequency and intensity of summer droughts will increase in the course of global climate change.

Recent spring phenology shifts in western C entral E urope based on multiscale observations - Yongshuo H. Fu; Shilong Piao; Maarten Op de Beeck; Nan Cong; Hongfang Zhao; Yuan Zhang; Annette Menzel; Ivan A. Janssens (Global Ecology and Biogeography, 2014)
Aim Although numerous studies have reported advanced N orthern H emisphere spring phenology since the 1980s, recent studies based on remote sensing have reported a reversal or deceleration of this trend. This study aimed (1) to fully understand recent spring phenology shifts using both in situ observations and satellite‐based normalized difference vegetation index ( NDVI ) datasets, and (2) to test whether the NDVI methods capture the trends observed in situ. Location W estern C entral E urope. Methods Temporal spring phenology trends (leaf unfolding dates) were examined using 1,001,678 in situ observations of 31 plant species at 3984 stations, as well as NDVI ‐based start‐of‐season dates, obtained using five different methods, across the pixels that included the phenology stations. Results In situ and NDVI observations both indicated that spring phenology significantly advanced during the period 1982–2011 at an average rate of −0.45 days yr −1 . This trend was not uniform across the period and significantly weakened over the period 2000–2011. Furthermore, opposite trends were found between in situ and NDVI observations over the period 2000–2011. Averaged over all species, the in situ observations indicated a slower but still advancing trend for leaf unfolding, whereas the NDVI series showed a delayed spring phenology. Main conclusions The recent trend reversal in the advancement of spring phenology in western C entral E urope is likely to be related to the response of early spring species to the cooling trend in late winter. In contrast, late spring species continued to exhibit advanced leaf unfolding, which is consistent with the warming trend during spring months. Because remote sensing does not distinguish between species, the signal of growing‐season onset may only reflect the phenological dynamics of these earliest species in the pixel, even though most species still exhibit advancing trends.

Changes in first flowering dates and flowering duration of 232 plant species on the island of Guernsey - Anna Bock; Tim H. Sparks; Nicole Estrella; Nigel Jee; Andrew Casebow; Christian Schunk; Michael Leuchner; Annette Menzel (Global Change Biology, 2014)
Climate change has affected plant phenology; increasing temperatures are associated with advancing first flowering dates. The impact on flowering duration, however, has rarely been studied. In this study, we analysed first flowering dates and flowering durations from a 27 year dataset of weekly flower observations on 232 plant species from the island of Guernsey in the English Channel. The aim of this study was to explore variation in trends and relationships between first flowering dates, flowering duration and temperature. We specifically looked for evidence that traits, such as life forms and phylogenetic groups, explained variation in sensitivity of first flowering and flowering duration among species. Overall trends revealed significantly earlier flowering over time, by an average of 5.2 days decade −1 since 1985. A highly significant shortening of flowering duration was observed by an average of 10 days decade −1 . Correlations between first flowering, flowering duration and year varied between different species, traits and flowering periods. Significant differences among traits were observed for first flowering and to a lesser degree for flowering duration. Overall, in comparison to first flowering, more species had significant trends in flowering duration. Temperature relationships revealed large differences in strength and direction of response. 55% of the species revealed a significant negative relationship of first flowering dates and temperature. In contrast, only 19% of flowering durations had a significant negative temperature relationship. The advance in first flowering date together with a shortening of flowering duration suggests potentially serious impacts on pollinators, which might pose a major threat to biodiversity, agriculture and horticulture. Human health, in terms of pollen allergies, however, might benefit from a shortening of specific plant pollen seasons.

Erratum to: A comparison of methods to estimate seasonal phenological development from BBCH scale recording - Christine Cornelius; Hannes Petermeier; Nicole Estrella; Annette Menzel (International Journal of Biometeorology, 2014)

Frequency of inversions affects senescence phenology of Acer pseudoplatanus and Fagus sylvatica - Christina Schuster; Manfred Kirchner; Gert Jakobi; Annette Menzel (International Journal of Biometeorology, 2014)

Chilling outweighs photoperiod in preventing precocious spring development - Julia Laube; Tim H. Sparks; Nicole Estrella; Josef Höfler; Donna P. Ankerst; Annette Menzel (Global Change Biology, 2014)
It is well known that increased spring temperatures cause earlier onset dates of leaf unfolding and flowering. However, a temperature increase in winter may be associated with delayed development when species' chilling requirements are not fulfilled. Furthermore, photosensitivity is supposed to interfere with temperature triggers. To date, neither the relative importance nor possible interactions of these three factors have been elucidated. In this study, we present a multispecies climate chamber experiment to test the effects of chilling and photoperiod on the spring phenology of 36 woody species. Several hypotheses regarding their variation with species traits (successional strategy, floristic status, climate of their native range) were tested. Long photoperiods advanced budburst for one‐third of the studied species, but magnitudes of these effects were generally minor. In contrast to prior hypotheses, photosensitive responses were not restricted to climax or oceanic species. Increased chilling length advanced budburst for almost all species; its effect greatly exceeding that of photoperiod. Moreover, we suggest that photosensitivity and chilling effects have to be rigorously disentangled, as the response to photoperiod was restricted to individuals that had not been fully chilled. The results indicate that temperature requirements and successional strategy are linked, with climax species having higher chilling and forcing requirements than pioneer species. Temperature requirements of invasive species closely matched those of native species, suggesting that high phenological concordance is a prerequisite for successful establishment. Lack of chilling not only led to a considerable delay in budburst but also caused substantial changes in the chronological order of species' budburst. The results reveal that increased winter temperatures might impact forest ecosystems more than formerly assumed. Species with lower chilling requirements, such as pioneer or invasive species, might profit from warming winters, if late spring frost events would in parallel occur earlier.

Using phenology to assess urban heat islands in tropical and temperate regions - Susanne Jochner; Milene Alves‐Eigenheer; Annette Menzel; Leonor Patrícia C. Morellato (International Journal of Climatology, 2013)
The study of urban phenology is relevant to assess the effects of heat islands and the potential impacts of climate change on plants. Temperature is the main factor regulating plant development in moist/temperate regions. However, plants in tropical cities may respond to additional environmental cues, such as air humidity. We examined whether differences in air temperature and humidity along an urban–rural gradient influenced phenological onset dates of trees in a temperate mid‐latitude city (Munich, Germany) and a city in the neotropics (Campinas, Brazil). (Dis)similarities were identified incorporating equivalent study design based on identical methods for recording phenology and site‐specific meteorological data. We found that phenological onset dates of silver birch ( Betula pendula ) were able to describe local temperature variations in Munich. Correlation coefficients between mean temperature and onset dates of Betula were significant and varied between r = −0.48 and r = −0.72. However, onset dates for yellow trumpet tree ( Tabebuia chrysotricha ), false Brazilwood ( Caesalpinia pluviosa ) and rosewood ( Tipuana tipu ) in Campinas were rather variable, and the magnitude and significance of correlation coefficients with temperature varied greatly among species/phenophases. Nevertheless, we detected significant correlations, especially between Tipuana phenophases and temperature and between leaf unfolding of Tabebuia and humidity. Our findings revealed that the phenology of Tipuana was sufficiently sensitive to detect urban heat island effects in Campinas and might be a useful indicator of temperature variations and, in turn, of global warming. Because Tipuana is widely used for urban arborization in South America, we foresee many applications for monitoring heat islands in the neotropics. Furthermore, the fact that most phenophases of Tabebuia were not responsive to temperature stressed the importance of humidity variables. Additional species and phenophases should be explored to identify the further potential of phenology for monitoring heat islands in tropical cities.

Changes in the timing of hay cutting in Germany do not keep pace with climate warming - Anna Bock; Tim H. Sparks; Nicole Estrella; Annette Menzel (Global Change Biology, 2013)
A unique long‐term phenological data set of over 110 000 records of 1st cutting dates for haymaking across Germany, spanning the years 1951–2011 was examined. In addition, we analyzed a long‐term data set in the beginning of flowering of meadow foxtail ( Alopecurus pratensis ) covering the last 20 years. We tested whether hay‐cutting dates (based on a human decision when to cut) showed trends, temperature relationships and spatial distribution similar to the development of this grassland species, and if these trends could be related to climate change. The timing of 1st hay cut was strongly influenced ( P P −1 ; P AES , which encourage later cutting) were likely to be responsible for the regional differences, while the general increase in AES appears to have confounded the overall trend in hay cutting in the last 20 years. Trends over time and responses to temperature were small relative to those associated with the phenology of meadow foxtail. The advance in phenology of this species is greater than the advance in hay cutting, implying that hay cutting may not be keeping pace with a changing climate, which may have a positive effect on grassland ecology.

The impacts of climate change on the winter hardiness zones of woody plants in Europe - Philipp Gloning; Nicole Estrella; Annette Menzel (Theoretical and Applied Climatology, 2013)

Recent and future climate extremes arising from changes to the bivariate distribution of temperature and precipitation in Bavaria, Germany - Nicole Estrella; Annette Menzel (International Journal of Climatology, 2013)
This study assesses recent and future changes in joint temperature and precipitation regimes at 28 sites in Bavaria, based on statistical downscaling of the ECHAM4 B2 Scenario (WETTREG). Monthly meteorological data of three future decades (2021–2030, 2031–2040 and 2041–2050) were compared with modelled data for the reference period 1971–2000. The bivariate data were classified into four weather types or modes (cooler/drier, cooler/wetter, warmer/wetter and warmer/drier relative to the 1971–2000 reference period). For the three future decades, a systematic change at all locations throughout the year was revealed. Both the cooler modes are predicted to occur less frequently in future decades; changes in warmer modes differ seasonally: In winter months, they are predicted to occur in the warmer/wetter mode, whereas in spring and summer months in the warmer/drier mode. Climatological extremes were defined as monthly weather events outside the 90% confidence ellipse of a Gaussian model of events in the reference period. An increase of extremes in the decade 2041–2050 was striking for June, which is predicted to be warmer and drier for half of the years. The same decade is predicted to experience the most extreme warm and wet modes, one in three Februarys and one in two winters are likely to be in this mode. The magnitude of these future changes in climate was related to the present mean annual temperature of the stations by rank regression. Stations with currently cooler climates are more likely to retain the normal conditions of the baseline period in contrast to currently warmer stations where the increase of extreme warm and wet conditions in summer and winter is expected to be larger. Copyright © 2012 Royal Meteorological Society

Large-scale genetic structure and drought-induced effects on European Scots pine (Pinus sylvestris L.) seedlings - Steffen Taeger; Barbara Fussi; Monika Konnert; Annette Menzel (European Journal of Forest Research, 2013)

A plant's perspective of extremes: terrestrial plant responses to changing climatic variability - Christopher P.O. Reyer; Sebastian Leuzinger; Anja Rammig; Annett Wolf; Ruud P. Bartholomeus; Antonello Bonfante; Francesca de Lorenzi; Marie Dury; Philipp Gloning; Renée Abou Jaoudé; Tamir Klein; Thomas M. Kuster; et al. (Global Change Biology, 2013)
We review observational, experimental, and model results on how plants respond to extreme climatic conditions induced by changing climatic variability. Distinguishing between impacts of changing mean climatic conditions and changing climatic variability on terrestrial ecosystems is generally underrated in current studies. The goals of our review are thus (1) to identify plant processes that are vulnerable to changes in the variability of climatic variables rather than to changes in their mean, and (2) to depict/evaluate available study designs to quantify responses of plants to changing climatic variability. We find that phenology is largely affected by changing mean climate but also that impacts of climatic variability are much less studied, although potentially damaging. We note that plant water relations seem to be very vulnerable to extremes driven by changes in temperature and precipitation and that heatwaves and flooding have stronger impacts on physiological processes than changing mean climate. Moreover, interacting phenological and physiological processes are likely to further complicate plant responses to changing climatic variability. Phenological and physiological processes and their interactions culminate in even more sophisticated responses to changing mean climate and climatic variability at the species and community level. Generally, observational studies are well suited to study plant responses to changing mean climate, but less suitable to gain a mechanistic understanding of plant responses to climatic variability. Experiments seem best suited to simulate extreme events. In models, temporal resolution and model structure are crucial to capture plant responses to changing climatic variability. We highlight that a combination of experimental, observational, and/or modeling studies have the potential to overcome important caveats of the respective individual approaches.

Flux-based ozone risk assessment for adult beech forests - Ludger Grünhage; Rainer Matyssek; Karl-Heinz Häberle; Gerhard Wieser; Ursula Metzger; Michael Leuchner; Annette Menzel; Jochen Dieler; Hans Pretzsch; Winfried Grimmeisen; Lothar Zimmermann; Stephan Raspe (Trees, 2012)

Spatio-temporal investigation of flowering dates and pollen counts in the topographically complex Zugspitze area on the German–Austrian border - Susanne Jochner; Chiara Ziello; Andreas Böck; Nicole Estrella; Jeroen Buters; Ingrid Weichenmeier; Heidrun Behrendt; Annette Menzel (Aerobiologia, 2012)

Comprehensive methodological analysis of long‐term changes in phenological extremes in Germany - Christoph Schleip; Donna P. Ankerst; Andreas Böck; Nicole Estrella; Annette Menzel (Global Change Biology, 2012)
This study reports on alterations in the magnitude and frequency of extremes in reproductive phenology using long‐term records (1951–2008) for plant species widely distributed across Germany. For each of fourteen indicator phases studied, time series of annual onset dates at up to 119 stations, providing 50–58 years of observation, were standardized by their station mean and standard deviation. Four alternative statistical models were applied and compared to derive probabilities of extreme early or late onset times for the phases: (1) Gaussian models were used to describe decadal probabilities of standardized anomalies, defined by data either falling below the 5th or exceeding the 95th percentile. (2) Semi‐parametric quantile regression was employed for flexible and robust modelling of trends in different quantiles of onset dates. (3) Generalized extreme value distributions ( GEV ) were fitted to annual detrended minima and maxima of standardized anomalies, and (4) Generalized Pareto distributions ( GPD ) were fitted to extremes defined as peaks over threshold. Probabilities of extreme early phenological events inferred from Gaussian models, increased on average from 3 to 12%, whereas probabilities of extreme late phenological events decreased from 6 to 2% over the study period. Based on quantile regressions, summer and autumn phases revealed a more pronounced advancing pattern than spring phases. Estimated return levels by GEV were similar for the GPD methods, indicating that extreme early phenological events of magnitudes 2.5, 2.8, and 3.6 on the detrended standardized anomaly scale would occur every 20 years for spring, summer and autumn phases, respectively. This corresponds to absolute onset advances of up to 2 months depending on the season and species. This study demonstrates how extreme phenological events can be accurately modelled even in cases of inherently small numbers of observations, and underlines the need for additional evaluation related to their impacts on ecosystem functioning.

The influence of altitude and urbanisation on trends and mean dates in phenology (1980–2009) - Susanne C. Jochner; Tim H. Sparks; Nicole Estrella; Annette Menzel (International Journal of Biometeorology, 2012)

Effects of recent warm and cold spells on European plant phenology - Annette Menzel; Holm Seifert; Nicole Estrella (International Journal of Biometeorology, 2011)

A comparison of methods to estimate seasonal phenological development from BBCH scale recording - Christine Cornelius; Hannes Petermeier; Nicole Estrella; Annette Menzel (International Journal of Biometeorology, 2011)

Bayesian analysis of changes in Radiosonde Atmospheric Temperature - Christoph Schleip; Annette Menzel; Volker Dose (International Journal of Climatology, 2009)
This paper describes long‐term changes of global atmospheric temperature, using a strict Bayesian approach which considers three different models to describe the time series: the constant model, the linear model and a change point model. The change point model allows the description of nonlinear annual rates of change with associated confidence intervals. We calculate the probabilities of each of the three models and average finally over these models to obtain the expected functional behaviour and rate of change in temperature with annual resolution. We apply this procedure to a new homogenized Radiosonde Atmospheric Temperature Products for Assessing Climate (RATPAC‐A) data set. Annual mean temperature for 13 pressure levels from the surface to 30 hPa is examined. Residual sums of squares reveal that Bayesian‐model‐averaged function descriptions and rates of changes are especially useful and informative for the surface, troposphere and tropopause and less appropriate for the stratosphere. From the surface up to the tropopause (200–100 hPa), the results reveal that the change point model provides the best data fit. Despite the occurrence of two volcanic eruptions El Chicón (1982) and Mt. Pinatubo (1991), the stratosphere (70–30 hPa) shows a preference for the linear model (60%). The near surface changes exhibit comparatively high change point probability around 1985 and 1995, whereas those at the tropopause level are highest between 1995 and 2000. For the surface and troposphere the model‐averaged functional behaviour increases quite constantly, whereas the model‐averaged functional behaviour for the tropopause decreases until the end of the 1990s and increases from 2000 onwards. The limitations of the currently used radiosonde data render interpretation of the observed changes difficult. Additionally undetected change points may result from our limited model space. In future it should be tested whether a multiple change point model provides a better data description for the stratosphere. Copyright © 2008 Royal Meteorological Society

Bayesian analysis of the species-specific lengthening of the growing season in two European countries and the influence of an insect pest - Annette Menzel; Nicole Estrella; Werner Heitland; Andreja Susnik; Christoph Schleip; Volker Dose (International Journal of Biometeorology, 2008)

Trends and temperature response in the phenology of crops in Germany - NICOLE ESTRELLA; TIM H. SPARKS; ANNETTE MENZEL (Global Change Biology, 2007)
The phenology of 78 agricultural and horticultural events from a national survey in Germany spanning the years 1951–2004 is examined. The majority of events are significantly earlier now than 53 years ago, with a mean advance of 1.1–1.3 days per decade. The mean trends for ‘true phases’, such as emergence and flowering, of annual and perennial crops are not significantly different, although more trends (78% vs. 46%) are significant for annual crops. We attempt to remove the influence of technological advance or altered farming practices on phenology by detrending the respective time series by linear regression of date (day number) on year. Subsequently, we estimate responses to mean monthly and seasonal temperature by correlation and regression in two ways; with and without removing the year trend first. Nearly all (97%) correlation coefficients are negative, suggesting earlier events in warmer years. Between 82% and 94% of the coefficients with seasonal spring and summer temperatures are significant. The conservative estimate (detrended) of mean temperature response against mean March–May temperature (−3.73 days °C −1 ) is significantly less than the full estimate (−4.31 days °C −1 ), the ‘true’ size of phenological temperature response may lie in between. Perennial crops exhibited a significantly higher temperature response to mean spring temperature than the annual crops.

Peptidomic analysis of human peripheral monocytes persistently infected by Chlamydia trachomatis - Birgit Krausse-Opatz; Annette Busmann; Harald Tammen; Christoph Menzel; Thomas Möhring; Nicolas Le Yondre; Cornelia Schmidt; Peter Schulz-Knappe; Henning Zeidler; Hartmut Selle; Lars Köhler (Medical Microbiology and Immunology, 2007)

European phenological response to climate change matches the warming pattern - ANNETTE MENZEL; TIM H. SPARKS; NICOLE ESTRELLA; ELISABETH KOCH; ANTO AASA; REIN AHAS; KERSTIN ALM‐KÜBLER; PETER BISSOLLI; OL'GA BRASLAVSKÁ; AGRITA BRIEDE; FRANK M. CHMIELEWSKI; ZALIKA CREPINSEK; et al. (Global Change Biology, 2006)
Global climate change impacts can already be tracked in many physical and biological systems; in particular, terrestrial ecosystems provide a consistent picture of observed changes. One of the preferred indicators is phenology, the science of natural recurring events, as their recorded dates provide a high‐temporal resolution of ongoing changes. Thus, numerous analyses have demonstrated an earlier onset of spring events for mid and higher latitudes and a lengthening of the growing season. However, published single‐site or single‐species studies are particularly open to suspicion of being biased towards predominantly reporting climate change‐induced impacts. No comprehensive study or meta‐analysis has so far examined the possible lack of evidence for changes or shifts at sites where no temperature change is observed. We used an enormous systematic phenological network data set of more than 125 000 observational series of 542 plant and 19 animal species in 21 European countries (1971–2000). Our results showed that 78% of all leafing, flowering and fruiting records advanced (30% significantly) and only 3% were significantly delayed, whereas the signal of leaf colouring/fall is ambiguous. We conclude that previously published results of phenological changes were not biased by reporting or publication predisposition: the average advance of spring/summer was 2.5 days decade −1 in Europe. Our analysis of 254 mean national time series undoubtedly demonstrates that species' phenology is responsive to temperature of the preceding months (mean advance of spring/summer by 2.5 days°C −1 , delay of leaf colouring and fall by 1.0 day°C −1 ). The pattern of observed change in spring efficiently matches measured national warming across 19 European countries (correlation coefficient r =−0.69, P

Integration of flowering dates in phenology and pollen counts in aerobiology: analysis of their spatial and temporal coherence in Germany (1992–1999) - Nicole Estrella; Annette Menzel; Ursula Krämer; Heidrun Behrendt (International Journal of Biometeorology, 2006)

Bayesian correlation between temperature and blossom onset data - VOLKER DOSE; ANNETTE MENZEL (Global Change Biology, 2006)
The recent quantification of changes in time series of phenology data with Bayesian methods has provided compelling evidence for changes during the last 20 years. In this paper we correlate the phenological observations with spring temperature time series. We provide quantitative answers to the question whether changes in temperature and phenological time series should be regarded as coherent or independent. For the three considered species snowdrops, cherry and lime tree we find factors of 1.05, 2.19 and 3.26, respectively, in favor of coherence. The functional behavior and the trend in the temperature time series are presented. They amount to 0.15°C yr −1 for the January–March average, 0.09°C yr −1 for February–April and 0.1°C yr −1 for March–May in 2002. In addition, we compare blossom trends for the coherent and independent hypotheses and find that the transition from trend values slightly positive before 1970 to strongly negative at present becomes sharper as the temperature data are included in the analysis.

Bayesian analysis of climate change impacts in phenology - Volker Dose; Annette Menzel (Global Change Biology, 2004)
The identification of changes in observational data relating to the climate change hypothesis remains a topic of paramount importance. In particular, scientifically sound and rigorous methods for detecting changes are urgently needed. In this paper, we develop a Bayesian approach to nonparametric function estimation. The method is applied to blossom time series of Prunus avium L., Galanthus nivalis L. and Tilia platyphyllos SCOP. The functional behavior of these series is represented by three different models: the constant model, the linear model and the one change point model. The one change point model turns out to be the preferred one in all three data sets with considerable discrimination of the other alternatives. In addition to the functional behavior, rates of change in terms of days per year were also calculated. We obtain also uncertainty margins for both function estimates and rates of change. Our results provide a quantitative representation of what was previously inferred from the same data by less involved methods.

The European Phenology Network - Arnold J. H. van Vliet; Rudolf S. de Groot; Yvette Bellens; Peter Braun; Robert Bruegger; Ekko Bruns; Jan Clevers; Christine Estreguil; Michael Flechsig; François Jeanneret; Marta Maggi; Pim Martens; et al. (International Journal of Biometeorology, 2003)

Variations of the climatological growing season (1951–2000) in Germany compared with other countries - Annette Menzel; Gert Jakobi; Rein Ahas; Helfried Scheifinger; Nicole Estrella (International Journal of Climatology, 2003)
We analyse how variations in the climatological growing season, defined by single‐value thresholds of daily minimum and mean air temperature, mirror recent changes in plant phenological phases. In Germany (1951–2000, 41 climate stations), the dates of last spring frost T min A parallel evaluation of trends in the climatological growing season in other European countries (Austria, Switzerland, Estonia) supports this finding of a stronger lengthening of the frost‐free period than that of the growing season based on daily mean air temperature. The mean lengthening of the frost‐free period of 0.50 days per year in Austria and Switzerland (1951–99, 18 stations T mean ≥7 °C) in Austria and Switzerland (0.39 days per year) also approximates the respective result for Germany (0.36 days per year). However, in several cases, the trends increase with altitude (up to 500–900 m a.s.l.), but at high‐elevation climate stations (>950 m a.s.l.) weaker trends are again generally observed. Copyright © 2003 Royal Meteorological Society

Plant Phenological Anomalies in Germany and their Relation to Air Temperature and NAO - Annette Menzel (Climatic Change, 2003)

Atmospheric mechanisms governing the spatial and temporal variability of phenological phases in central Europe - Helfried Scheifinger; Annette Menzel; Elisabeth Koch; Christian Peter; Rein Ahas (International Journal of Climatology, 2002)
A data set of 17 phenological phases from Germany, Austria, Switzerland and Slovenia spanning the time period from 1951 to 1998 has been made available for analysis together with a gridded temperature data set (1° × 1° grid) and the North Atlantic Oscillation (NAO) index time series. The disturbances of the westerlies constitute the main atmospheric source for the temporal variability of phenological events in Europe. The trend, the standard deviation and the discontinuity of the phenological time series at the end of the 1980s can, to a great extent, be explained by the NAO. A number of factors modulate the influence of the NAO in time and space. The seasonal northward shift of the westerlies overlaps with the sequence of phenological spring phases, thereby gradually reducing its influence on the temporal variability of phenological events with progression of spring (temporal loss of influence). This temporal process is reflected by a pronounced decrease in trend and standard deviation values and common variability with the NAO with increasing year‐day. The reduced influence of the NAO with increasing distance from the Atlantic coast is not only apparent in studies based on the data set of the International Phenological Gardens, but also in the data set of this study with a smaller spatial extent (large‐scale loss of influence). The common variance between phenological and NAO time series displays a discontinuous drop from the European Atlantic coast towards the Alps. On a local and regional scale, mountainous terrain reduces the influence of the large‐scale atmospheric flow from the Atlantic via a proposed ‘decoupling mechanism’. Valleys in mountainous terrain have the inclination to harbour temperature inversions over extended periods of time during the cold season, which isolate the valley climate from the large‐scale atmospheric flow at higher altitudes. Most phenological stations reside at valley bottoms and are thus largely decoupled in their temporal variability from the influence of the westerly flow regime (local‐scale loss of influence). This study corroborates an increasing number of similar investigations that find that vegetation does react in a sensitive way to variations of its atmospheric environment across various temporal and spatial scales. Copyright © 2002 Royal Meteorological Society.

Phenology: Its Importance to the Global Change Community - Annette Menzel (Climatic Change, 2002)

Spatial and temporal variability of the phenological seasons in Germany from 1951 to 1996 - Annette Menzel; Nicole Estrella; Peter Fabian (Global Change Biology, 2001)
Various indications for shifts in plant and animal phenology resulting from climate change have been observed in Europe. This analysis of phenological seasons in Germany of more than four decades (1951–96) has several major advantages: (i) a wide and dense geographical coverage of data from the phenological network of the German Weather Service, (ii) the 16 phenophases analysed cover the whole annual cycle and, moreover, give a direct estimate of the length of the growing season for four deciduous tree species. After intensive data quality checks, two different methods – linear trend analyses and comparison of averages of subintervals – were applied in order to determine shifts in phenological seasons in the last 46 years. Results from both methods were similar and reveal a strong seasonal variation. There are clear advances in the key indicators of earliest and early spring (−0.18 to −0.23 d y −1 ) and notable advances in the succeeding spring phenophases such as leaf unfolding of deciduous trees (−0.16 to −0.08 d y −1 ). However, phenological changes are less strong during autumn (delayed by + 0.03 to + 0.10 d y −1 on average). In general, the growing season has been lengthened by up to −0.2 d y −1 (mean linear trends) and the mean 1974–96 growing season was up to 5 days longer than in the 1951–73 period. The spatial variability of trends was analysed by statistical means and shown in maps, but these did not reveal any substantial regional differences. Although there is a high spatial variability, trends of phenological phases at single locations are mirrored by subsequent phases, but they are not necessarily identical. Results for changes in the biosphere with such a high resolution with respect to time and space can rarely be obtained by other methods such as analyses of satellite data.

Spatial and temporal variability of the phenological seasons in Germany from 1951 to 1996 - Annette Menzel; Nicole Estrella; Peter Fabian (Global Change Biology, 2001)

Wie sehen die Wälder von morgen aus — aus der Sicht eines Klimatologen - Peter Fabian; Annette Menzel (European Journal of Forest Research, 1998)